2021
DOI: 10.3390/met11060949
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ni–Al-Based Materials: Strength and Combustion Behavior

Abstract: The effect of PTFE, continuous boron, and tungsten fibers on the combustion behavior and strength of reactive Ni–Al compacts was examined in this study. The introduction of continuous fibers into Ni–Al compacts according to the developed scheme was found to increase the flexural strength from 12 to 120 MPa. Heat treatment (HT), leading to chemical interaction of the starting components, increases the strength of compacts at temperatures not exceeding 550 °C. The combination of reinforcement and HT significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The milled powders were pressed with uniaxial pressure in a steel die into cylindrical samples ( Figure 1 ) with relative densities in the range of 65–70% of the maximum theoretical value. In [ 34 ], experiments with the SWL of Ni–Al powder samples (10 mm in diameter and height) were conducted. The results of the experiments showed that it is possible to initiate an exothermic reaction in the powder sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The milled powders were pressed with uniaxial pressure in a steel die into cylindrical samples ( Figure 1 ) with relative densities in the range of 65–70% of the maximum theoretical value. In [ 34 ], experiments with the SWL of Ni–Al powder samples (10 mm in diameter and height) were conducted. The results of the experiments showed that it is possible to initiate an exothermic reaction in the powder sample.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the experiments showed that it is possible to initiate an exothermic reaction in the powder sample. Given this, the size, composition, and properties of the cylindrical samples were taken from [ 34 ]. In addition, two through holes were drilled (2.5 mm and 5 mm in diameter) in the center of both Ni-Al powder cylindrical samples.…”
Section: Methodsmentioning
confidence: 99%
“…The specimens were placed in a 20 L reactor [48]. The experiments were conducted in argon and air at atmospheric pressure, as well as in vacuum at 2 × 10 4 Pa. A flat graphite heater was used to create a flat combustion front.…”
Section: Methodsmentioning
confidence: 99%
“…The combustion process was recorded with a video camera (HC-VC770, Panasonic, Osaka, Japan) at a frame rate of 50 fps. The specimens were placed in a 20 L reactor [48]. The experiments were conducted in argon and air at atmospheric pressure, as well as in vacuum at 2 × 10 4 Pa. A flat graphite heater was used to create a flat combustion front.…”
Section: Methodsmentioning
confidence: 99%
“…Metallic energetic composites can release a large amount of heat under high-speed impact or high temperature conditions to produce severe damage effects, so they have received extensive attention from the military and petroleum industries. Among them, Al/Ni energetic composites have high specific strength and high energy release capacity in theory and have important potential applications in active fragments and reaction liners. As a reaction material, Al/Ni energetic composites release energy in the form of heat only under high temperature or high impact load conditions. Therefore, at present, many scholars are looking for the improvement of ignition sensitivity, mainly in the following three ways: (1) using particles to increase the contact area between Al and Ni and shorten the diffusion reaction distance as much as possible, (2) reducing the effect of oxide layer and adsorption layer on the exothermic reaction, and (3) increasing the plastic deformation of the material to increase the internal stress of the material. Cold spraying is a process that accelerates metal particles to supersonic and then impact on the substrate through mechanical occlusion between severely deformed metal particles , and ballistic feature embedding to achieve additive manufacturing. , This process can not only further increase the contact area between particles and the internal stress of the material through the plastic deformation of the particles but also the high-speed impact of the particles will break the metal oxide film at the interface and make the fresh metal directly contact. Therefore, Al/Ni energetic composites prepared by cold spraying have a high ignition sensitivity.…”
Section: Introductionmentioning
confidence: 99%